A new immunosuppressive pregnane glycoside from aqueous fraction of Epigynum cochinchinensis. Issue 24 (17th December 2017) - Wan, Zong; Yao, Yuan-Cheng; Gao, Fei; Cai, Sheng-Bao; Khan, Afsar; Zhao, Tian-Rui; Yang, Xiao-Yan; Fan, Jian; Qian, Sheng-Yan; Cao, Jian-Xin; Cheng, Gui-Guang
Abstract: Chemical investigation on the aqueous fraction of the stems of Epigynum cochinchinensis led to the isolation of a new pregnane glycoside named as epigycoside A (1 ) along with three known analogues (2 –4 ). The structure of compound1 was elucidated by means of spectroscopic techniques, including HRESIMS, and 1D and 2D NMR experiments. The immunosuppressive activity of1 was evaluated by an in vitro model of concanavalin A-induced mice splenocytes proliferation. Compound1 showed significant inhibitory activity in a dose-dependent manner, closer to the efficacy of positive control, dexamethasone, at a concentration of 50 μM. Abstract :